Морфологія частинок та текстурні характеристики нанокремнезему, гідро-ущільненого при різних ступенях гідратації - Gun’ko, V. M.; Turov, V. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2023)
The particulate morphology and textural characteristics of nanosilica A–300, initial and hydro-compacted        (cA–300) by wetting with various amounts of water in the range of h = 0.5–5.0 g per gram of dry silica, strongly stirred and then dried, have been analyzed using low-temperature 1H NMR spectroscopy (treated-dried-wetted samples), small angle X-ray scattering, scanning and transmission electron microscopies, infrared spectroscopy, and nitrogen adsorption methods (treated-dried-degassed samples). The effects of the hydro-compaction of A-300 depend strongly on the wetting degree with maximum changes at h = 1.5–2.0 g/g. The wetting degree could be varied to control the reorganization of aggregates of nonporous nanoparticles (NPNP, which are composed of tightly packed adherent proto-particles or nuclei) and agglomerates of aggregates (secondary and ternary structures, respectively), as well as visible particles; i.e., there is a penta-level structural hierarchy of nanosilica with three-level supra-NPNP structures. The hydro-compaction is accompanied by non-monotonic changes in the morphological and textural characteristics of cA–300 vs. h. However, the nanoparticles are much weaker affected by the treatment than higher hierarchical structures. At h ? 1 g/g, the reorganization of aggregate/agglomerate structures does not lead to diminution of the specific surface area (SSA); however, at h ? 1.5 g/g, the SSA value decreases, but the pore volume (estimated from nitrogen adsorption) increases despite the empty volume (estimated from the bulk density rb) of the powder decreases from 21.8 cm3/g for initial A–300 (rb = 0.045 g/cm3) to 3.45 cm3/g on hydro-compaction at h = 4.5 g/g (rb = 0.256 g/cm3), pores become more ordered with a predominant contribution of cylindrical shapes. The textural reorganization of dried hydro-compacted nanosilica is possible again after addition of new water amount. This suggests that the chemical bonds between neighboring nanoparticles do not practically form upon the hydro-compaction and subsequent drying. Thus, hydro-compacted nanosilica loses a dust-forming property (since rb strongly increases), but it remains active with respect to the NPNP mobility, e.g., in aqueous media, and the possibility of the reorganization of the supra-NPNP structures remains under various external actions that is of importance from a practical point of view.